The Transformation of the Teaching Factory as an Educational Tourism Attraction at Jember State Polytechnic - Suharsono, Degita Danur; Kamal, Mushthofa; Junaedi, Rusli Akhmad; Indartin, Tri Rafika Diyah; Diartika, Firda; Nurazizah, Nabila Febriyanti (P3M Politeknik Negeri Jember, 2025)
This study aims to analyze the transformation of the Teaching Factory (TeFa) concept at Jember State Polytechnic as an educational tourism attraction that can provide added value for educational institutions, students, and the community. TeFa, which initially functioned as a production and service-based learning model, has the potential to be developed into an educational tourism destination through the integration of vocational practices with knowledge-based tourism experiences. The study used a qualitative approach with a case study method, involving field observations, interviews with lecturers, students, and TeFa managers, as well as documentation of production and service activities. The results show that the transformation of TeFa into an educational tourism destination has a positive impact on improving student competencies, expanding partnership networks with industry, and opening opportunities for an education-based creative economy. Furthermore, the involvement of the surrounding community has also increased through participation in the provision of tourism support services. In conclusion, the Teaching Factory is not only effective as a vocational learning facility but also has strategic potential as a sustainable educational tourism destination within Jember State Polytechnic.